Institutional traps in the sphere of higher education - A. A. Zhuk (Russian Journal of Economics and Law)
Objective: to test the sphere of higher education for the presence of institutional traps under deep transformation of higher education and science in Russia, which may reduce the efficiency of their functioning.Methods: narrative analysis based on the analysis of behavioural practices of economic agents identified in various publications and presenting the author’s direct speech in regard to certain scientific and practical problems within the framework of institutional economic theory methodology.Results: theoretical approaches are reviewed to the interpretation of “institutional trap” phenomenon, which demonstrated the evolution of this category from the “blocking effect” in the English scientific economic literature to sustainable inefficient institution in the Russian segment of economic theory. It is revealed that one of the most discussed issues is inefficient transformation of institutions, and identification of its causes. Researchers’ ideas about some types of institutional traps inherent in the Russian economy are systematized.Based on the analysis of narratives, a large-scale study of behavioural practices of economic agents was carried out, as a result of which groups of institutional traps in the Russian higher education and science were identified and classified. It is established that the imperfection of the education financing causes problems in the system of labour remuneration and research grants. The fragmentation and inconsistency of managerial decisions led to the transformation of post-graduate course into a level of higher education, which violates the logic of scientific personnel training. A trap of metrics is the systemic orientation to assessment criteria, ranking and other quantitative indicators, leading to substitution of quality for quantity. Orientation to digitalization and informatization of the educational process has led to the transformation of education into a mechanism of mere information transfer. Scientific novelty: based on the conducted deep narrative analysis, the most characteristic groups of institutional traps inherent in the Russian sphere of higher education and science are identified and described, such as financial traps, administrative traps, metric traps, informatization and digitalization traps, as well as the systemic motivational trap based on the effect of asymmetry of the institutional motivation of market agents.Practical significance: the obtained results can be used to correct the state policy in the field of higher education and science in the direction of elimination and prevention of institutional traps in order to improve its efficiency, as well as in the development of various programs for the development of this sphere by public authorities.